Pengembangan Video Pembelajaran Berbasis Power Director: Upaya Peningkatan Kemampuan Komunikasi Matematis Dan Kemandirian Belajar Siswa Pada Masa Pademi Covid-19 - Dwi Yuliastuti; Ummu Sholihah (Sekolah Tinggi Ilmu Tarbiyah (STIT) Aqidah Usymuni, 2021)
AbstractOnline teaching and learning is a learning experience that must be passed by teachers and studentsduring the Covid-19 pandemic, therefore teachers are required to be able to make learning mediathat are interesting and understandable by students. This study aims to describe the development ofpower director-based learning videos on social arithmetic material in improving students'mathematical communication skills and independence. This study uses descriptive quantitativeresearch methods. The population of this research is class VII MTsN 7 Nganjuk, consisting of classVIIA as the experimental class and Class VII B as the control class, chosen by using the samehomogeneity technique. The design used in this study was the design of the pretest control groupand the post test group. The target of this research is online learning using digital media powerdirector as a medium of learning given to 32 students of class VII A as an experimental class and32 students of class VIIB as a control class at MTsN 7 Nganjuk. The results of this study indicatethat developing learning using power director-based media can improve students' mathematicalcommunication skills, but does not increase student learning independence, and there is norelationship between students' mathematical communication skills and student learningindependence in classes using power director-based learning media. .Keywords: Media development, Mathematical communication skills and student learningindependence.